2023
DOI: 10.1007/s00330-023-09788-6
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion coefficient correlates with different histopathological features in several intrahepatic tumors

Alexey Surov,
Kai Ina Eger,
Johann Potratz
et al.

Abstract: Objectives To investigate associations between apparent diffusion coefficient (ADC) and cell count, Ki 67, tumor-stroma ratio (TSR), and tumoral lymphocytes in different hepatic malignancies. Methods We identified 149 cases with performed liver biopsies: hepatocellular cancer (HCC, n = 53), intrahepatic cholangiocarcinoma (iCC, n = 29), metastases of colorectal cancer (CRC, n = 24), metastases of breast cancer (BC, n = 28), and metastases of pancreatic can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Consistent with prior studies, our study revealed no associations between the ADC and other adverse clinicopathological features, such as tumor size, location, lymph node metastases, and R-status [ 16 , 18 ]. Interestingly, in pancreatic cancer liver metastases, the ADC also did not predict relevant histopathological features [ 31 ]. In agreement with Sakane et al and Dunet et al, our study found no significant prognostic value for the ADC [ 10 , 32 ], while other studies found better OS in patients with tumors exhibiting high ADC values compared to those with low ADC values [ 14 , 18 , 19 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with prior studies, our study revealed no associations between the ADC and other adverse clinicopathological features, such as tumor size, location, lymph node metastases, and R-status [ 16 , 18 ]. Interestingly, in pancreatic cancer liver metastases, the ADC also did not predict relevant histopathological features [ 31 ]. In agreement with Sakane et al and Dunet et al, our study found no significant prognostic value for the ADC [ 10 , 32 ], while other studies found better OS in patients with tumors exhibiting high ADC values compared to those with low ADC values [ 14 , 18 , 19 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, Surov et al present original associations between ADC values carefully measured at the biopsy site and cell count, tumor stromal ratio (TSR), and proliferation KI 67 index in different types of liver tumors > 5 mm, with good interobserver ADC measurement reproducibility [8]. In this retrospective study including 149 patients, statistically significant, however moderate, rank correlation coefficients were demonstrated between ADC and histopathologic features in HCC, intrahepatic cholangiocarcinoma, metastases of colorectal cancer, and breast cancer, while no correlation was found in pancreatic cancer metastases.…”
mentioning
confidence: 99%